Cinematic Desire and Fantasy in Adolfo Bioy Casares' La Invención De Morel (1940) - Amanda Parente Vieira; Cláudio Augusto Carvalho Moura (Instituto Federal de Educação, Ciência e Tecnologia do Piauí, 2024)
This paper aims to analyze the relationship between the concepts of desire and fantasy, as understood by Lacanian theory, and their manifestation in cinema. In order to do so, it explores and discusses cinema's influence over literature, focusing on how this relationship is reflected in the novel La Invención de Morel ([1940] 1953), written by Argentinian author Adolfo Bioy Casares. The analysis employs scholarship from film critics McGowan (2007), Metz (1982), Zizek (1989, 2006), Mulvey (1975, 1989), and others through the lens of Psychoanalytic Film Theory.